Employing the professional competencies of the communicator to develop work in Saudi digital newsrooms: A field study (The International Journal of Educational Sciences and Arts, 2025)
The research aimed to study the employment of the professional competencies of the communicator to develop the work in Saudi digital newsrooms, by identifying the features of the media work environment in digital newsrooms in Saudi press institutions, monitoring the similarities and differences in the nature of the impact of the features of the media work environment in digital newsrooms on the development of the professional competencies of the communicator, revealing the professional competencies employed by the communicator to develop work in digital newsrooms, and identifying the pressures to which the communicator is exposed in Saudi press institutions. The study relied on the survey methodology, applying to a sample of journalists working in digital newsrooms amounting to (115) items using the questionnaire tool, as well as a sample of senior management in press institutions amounting to (5) items using the in-depth interview.The results revealed an increase in the adoption by journalists of the study sample of various competencies in digital newsrooms, of all kinds (knowledge competencies -organizational competencies - technical competencies -skill competencies -ethical competencies). The study also revealed the irregularity of press institutions in providing professional training to develop work competencies in digital newsrooms, while their employees are exposed to pressures, foremost of which are (the absence of financial support for the communicator -the lack of incentives from the institution -the absence of a clear vision for the institution to develop work and workers). It also concluded that the communicator needs to develop a number of competencies to work in digital newsrooms, foremost of which are the personal and professional qualities that the journalist acquired during his work in the field before he turned to newsrooms, from the possibility of benefiting from sources on the Internet to build professional competencies in digital newsrooms by inferring through those sources the direction in which public opinion trends are going, the impact of events and the paths of change. The study recommended that the journalist be keen to deal with modern technologies, three-dimensional, virtual reality and augmented reality, and use them to improve the experience of readers and viewers and attract them to news content.
Keywords: Professional Competencies; Communicator; Business Development; Saudi Digital Newsrooms